INTERDISCIPLINARY APPROACH IN ESP PEDAGOGY FOR PROMOTING LEARNER’S PROFESSIONAL LEXICAL COMPETENCE - Kurbanova, Husniya (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The pedagogical value of authentic materials in language education has been extensively recognized and debated since the late 19th century, garnering significant attention from researchers and educators across various fields. Despite the theoretical support for using authentic materials, their practical implementation in language teaching has progressed relatively slowly. Textbooks must often address the complexities and demands of integrating such materials effectively. This study investigates the benefits and challenges associated with incorporating authentic materials, such as real-life conversations, authentic texts, and case studies based on the TermoCLIL approach in English for specific classes. The effectiveness of this approach was assessed using an online survey from both students and teachers, emphasising using authentic reading materials specialized to Math students. The findings indicate that authentic materials and academic contexts significantly enhance learner interest and engagement. The research was conducted with first-year math students learning English for a specific purpose at Gulistan State University, and it focused on integrating authentic materials at the B1 proficiency level. A selection of educational resources, including textual and practical, was designed to create meaningful and communicative contexts and was implemented in classroom settings.
Keywords: authentic materials; ESP; reading; TermoCLIL; terminology; professional lexicon; Mathematics; authentic texts; CBI; Task-based instruction